Investigating Pre-treatment Effects and Optimising Solid-State Fermentation for Cellulase Production by Aspergillus niger MBL using Local Pineapple Leaves - Alexandra Cheryl, Anak Dennis (Universiti Malaysia Sarawak, 2025)
Agricultural wastes are the by-products generated as the result of cultivation and processing of raw agricultural products, in which accumulation of these wastes in the landfills without proper waste management can be a concerning issue to the society and environment. Pineapple leaves which are wastes produced from pineapple farming, have the potential to be utilised as raw materials in various biochemical processes such as solid-state fermentation in producing industrial important enzymes, particularly, cellulase. The applications of cellulases in various industries are enormous, however, high production cost of the chemically-produced cellulases has been a major concern among the researchers in order to produce cheaper resource with improved sustainability for the industries. Production of cellulases by microorganisms such as filamentous fungi through solid-state fermentation has been broadly studied and showing a great potential as an alternative approach in producing enzymes with cheaper production cost. In this present study, pineapple leaves from a local cultivar known as ‘Nanas Paun’ were utilised as the substrate used in solid-state fermentation for the production of cellulase by Aspergillus niger MBL. The focus of the study was to evaluate the impacts of different pre-treatments on the morphological changes and lignocellulosic contents of the leaves, as well as, to identify the optimum conditions of the solid-state fermentation for cellulase production with high activity from the fungus mentioned using local pineapple leaves. Due to the complex physicochemical structure and compositional make-up of the biomass, the ‘Nanas Paun’ leaves were subjected to various pre-treatment methods such as chemical treatments with different concentration of dilute acid and alkaline solutions, as well as thermal treatment by autoclave. The effects of different pre-treatments on the compositional contents and morphological properties of the ‘Nanas Paun’ leaves were evaluated through a compositional analysis by gravimetric method and Scanning Electron Microscopy. It was suggested that pre-treatment of local pineapple leaves with 1.5% (v/v) hydrochloric solution revealed to be the most effective pre-treatment method as highest amount of cellulose (51.5% w/w) and lowest lignin content (10.3% w/w) were recorded, as well as showing the most notable changes and severe alteration on its morphological surface structure, in comparison with other pre-treatment methods. The ‘Nanas Paun’ leaves treated with 1.5% (v/v) hydrochloric acid solution was then utilised as the substrate for further evaluation on optimal conditions required for maximum cellulase production of high enzyme activity by Aspergillus niger MBL. Few parameters influencing solid-state fermentation such as incubation period, initial moisture content, pH, and temperature were optimised. Filter paper assay method was used to determine the total enzyme activity of cellulase, and reducing sugars released was assessed through dinitrosalicylic acid method. In this research study, it is concluded that the highest total cellulase activity was recorded at 5.1773 ± 1.2756 U, with treated ‘Nanas Paun’ leaves as the substrate, an incubation period of 8 days (192 hours), an initial moisture content of 70% (v/w), a pH of 5.0, and an incubation temperature at 35 °C. The findings of this study show the potential of local pineapple leaves to be employed as raw materials in bioconversion process such as fermentation to produce cellulase efficiently, with promising benefits for sustainable waste management.